Anti-oxidative hormetic effects of cellular autophagy induced by nutrient deprivation in a molluscan animal model. (April 2020) - Moore, M.N.; Shaw, J.P.; Pascoe, C.; Beesley, A.; Viarengo, A.; Lowe, D.M.
Abstract: This investigation using a molluscan animal model tested the hypothesis that experimentally induced lysosomal autophagy protects against oxidative cell injury. Induction of augmented lysosomal autophagy has previously been implicated in this protective process. Four treatment groups of blue mussels ( Mytilus galloprovincialis ) were used: Group 1 (fed - control), Group 2 (fasted), Group 3 (copper + fed) and Group 4 (copper + fasted). Groups 2 and 4 were fasted in order to trigger autophagy; and samples of hepatopancreas (liver analogue or digestive gland) from all 4 groups were taken at 3, 6 and 15 days. Treatment with copper provided a positive reference for oxidative stress: Groups 3 and 4 were treated with copper (10 μg Cu 2+ /animal/day) for three days only. Oxidative damage and cellular injury in hepatopancreatic digestive cells was found to decrease in Group 2 (fasted) compared to Group 1 (fed - control). Group 3 (fed + copper) showed clear evidence of oxidative stress and cell injury, as well as induction of antioxidant activities. Group 4 (copper + fasted) had a reduced uptake of copper and toxicity of copper was also reduced, compared with Group 3. It was concluded that augmented autophagy had a hormetic cytoprotective anti-oxidant effect. Graphical abstract: Image 1 Highlights: Antioxidant cytoprotective effects of fasting. Cell injury assessed using biomarkers for lysosomal function. Autophagy induced by nutrient deprivation. Copper induced oxidative stress. Augmented autophagy as a mechanism of hormesis.